Criminal Liability of an Accused Who Commit Obstruction of Justice - Itok Dwi Kurniawan (Publikasi Inspirasi Indonesia, 2023)
The criminal justice system is run by law enforcement officers who have authority based on law. All kinds of actions carried out by law enforcement officers are legal as long as they do not conflict with statutory regulations. So any form of obstruction of the judicial process is a violation of the law. This article will discuss problems related to criminal acts of obstruction of justice processes which are not normatively limitatively determined in the formulation of articles of law. This article was written using normative legal research methods with a conceptual approach. The results of this research show that obstruction of the judicial process is a criminal act that has very broad elements, however what needs to be taken into account is that the parameter of obstruction of justice is the contamination of the dignity and worth of the judicial institution.